Information System Management and its Principles in the Qur'an. - Alfera Rahmawati; Anik Faseha; Aziranaini; Syafaatul Habib (Penerbit Hellow Pustaka, 2025)
The author created this article with the aim of enabling the reader to understand the whole of the detailed understanding of Systems, Information, and Management as well as its relationship with the understanding of the name Management Information System according to the Experts and to present the theory of the principles of Resource Management in the Qur'an by reference to some combinations of the Scriptures. This article uses qualitative methods through library literature. The results indicate that there is a link between systems, information, and management that the organization really needs to work Management Information System to manage managed information resources so that it can produce and update goods and services. At the same time we produce five principles that should be used in the implementation of Management Information Systems in the review of the Qur'an and its interpretation. Which is the first; Principles of Accuracy in Searching and Managing Information, Second; Transparency and Honesty in Management, Third; Managing Resources With Wisdom, Fourth; Fair Decision-making, and Fifth; Development and Innovation.